The concept of Hima and Harim in the application of mangrove ecosystem protagonist as potential ecological indicator for inorganic contaminants - Ramya, Razanah; Othman, Rashidi; Mohd. Yaman, Maheran (Institut Terjemahan & Buku Malaysia Berhad, 2016)
The increasing inorganic contaminants in mangrove ecosystem give the negative effect toward biotic components and human health. Mangrove is known as phylogenetic heterogeneous group that can adapt and deal the challenge in highly anoxic and saline environment that occupy about 181000km² of tropical and subtropical coastline. However, mangrove has been decline almost 20% to 35% in global scale since 1980 through the crucial matter such as climate changes, human development and population and water pollution. Mangrove forest perform as the sink for pollutant from inland freshwater or marine with variety of chemical distributed such as by agricultural, industrial, pesticides, domestic uses and petroleum. Phytoremediation process use to clean up metal and metalloid-contaminated in sediment and water as a cost effective and environmental friendly. Plants produce bacterial mercuric reductive and organ mercurial that can convert the toxic ion to metallic from the leaves surface. This paper provides broad overview of the evidence to support suitability and prospects of transgenic research in phytoindicator of mangrove ecosystem on heavy metals and metalloids.